A Semiparametric Test of Agent's Information Sets for Games of Incomplete Information - Salvador Navarro; Yuya Takahashi (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2012)
We propose semiparametric tests of misspecification of agent's information for games of incomplete information. The tests use the intuition that the opponent's choices should not predict a player's choice conditional on the proposed information available to the player. The tests are designed to check against some commonly used null hypotheses (Bajari et al. (2010), Aradillas-Lopez (2010)). We show that our tests have power to discriminate between common alternatives even in small samples. We apply our tests to data on entry in the US airline industry. Both the assumptions of independent and correlated private shocks are not supported by the data.
urn:nbn:de:bvb:19-epub-17381-6
Keywords: 330